Analysis of the clinical characteristics of pediatric patients who experience ifosfamide‐induced encephalopathy. Issue 12 (18th September 2019) - Ide, Yuichiro; Yanagisawa, Ryu; Kubota, Noriko; Sakashita, Kazuo; Tozuka, Minoru; Nakamura, Tomohiko; Honda, Takayuki
Abstract: Background: Several kinds of pediatric hematological and/or malignant diseases are treated with chemotherapy regimens including ifosfamide (IFO). IFO‐induced encephalopathy (IIE) is one of the serious side effects, but there is not enough evidence regarding the clinical features of IIE in children. Procedure: We performed a retrospective study on pediatric patients treated with chemotherapy regimens, including IFO, at a single center. We recorded the clinical characteristics of all patients; we compared the clinical characteristics between patients who developed IIE and those who did not. Results: In total, 88 patients received a chemotherapy regimen including IFO. IIE developed in seven patients (8.0%). The median age of patients at the time of IIE development was 4.3 (range 1.4‐6.5) years in the younger population. Six of seven patients with IIE improved with supportive therapy only; however, one patient died due to heart failure. Overall survival was not different between the two groups. Multivariable analysis revealed that the co‐administration of cisplatin (CDDP) or carboplatin (CBDCA) was a significant risk factor associated with IIE. Although there was no significant difference in laboratory data between the groups before chemotherapy, patients who developed IIE showed exacerbation in several laboratory tests, including those for renal and liver functions. Conclusions: Renal dysfunction caused by the combination of nephrotoxic agents (IFO and CDDP/CBDCA) seems to be important for the development of pediatric IIE. It was thought to be difficult to predict IIE onset based on laboratory data before the initiation of chemotherapy regimens; however, careful observation of laboratory data during IFO chemotherapy regimens may help predict IIE onset and facilitate early treatment.